79.1k views
0 votes
-6 + k/ 7= -3 Please help guys!

User Channing
by
5.0k points

2 Answers

2 votes

Answer:

k = 25

Explanation:

-6 + k/ 7= -3

To get rid of 7 we can multiply both sides by 7.

7(-6 + k/7) = 7(-3)

= -46 + k = - 21

To leave the variable by itself, cancel out the -46 by adding 46 to both sides.

k = 25

User Steharro
by
5.0k points
1 vote

Answer:

k=21

Step-by-step explanation:Let's solve your equation step-by-step.−6+k7=−3

Step 1: Simplify both sides of the equation.

−6+k7=−3−6+17k=−317k−6=−3

Step 2: Add 6 to both sides.

17k−6+6=−3+6

17k=3

Step 3: Multiply both sides by 7.

7*(17k)=(7)*(3)

k=21

(happy to help)

User Adammokan
by
4.8k points